FUTURE INTERVENTIONS: HASBRO PETS, MINDFULNESS, PREVAIL. (11th November 2018) - Albright, L; Tkatch, R; Keown, K; Schaeffer, J; Wicker, E
Abstract: In order to address social connectedness and loneliness, resilience, and optimism a number of other interventions are currently under development; Examples include the following: 1) Hasbro animatronic pets are being provided to 400 older adults to reduce loneliness and improve social connectedness and optimism. 2) An online mindfulness intervention has been developed to improve resilience, optimism, and social connectedness for 800 older adults. 3) An online coaching tool, "Prevail, " is being adapted to improve social connectedness.